The Princeton Guide to Ecology - Carpenter, Stephen R.; Levin, Simon A. (Book collections on Project MUSE., 2009)
Contains up-to-date articles on the most important topics within seven major areas: autecology, population ecology, communities and ecosystems, landscapes and the biosphere, conservation biology, ecosystem services, and biosphere management.